Mechanisms to change farmers' drought adaptation behaviors in Sistan and Baluchistan Province, Iran - Khoshnodifar, Zahra; Karimi, Hamid; Ataei, Pouria (Frontiers in Sustainable Food Systems, 2023)
Introduction Frequent droughts in Iran have imposed economic and social losses on farmers. To mitigate drought implications, farmers' behaviors should be shifted towards drought adaptation. This research mainly aimed to study mechanisms for changing farmers' drought adaptation behaviors in Sistan and Baluchistan Province. Methods The research was conducted among farmers in this province (N = 950). The sample whose size was estimated at 275 farmers by Krejcie and Morgan's table was taken by the stratified random sampling technique. The research instrument was a researcher-made questionnaire. Data were analyzed by SPSS23 and AMOS23 software. The comprehensive action determination model was validated by confirmatory factor analysis. Furthermore, structural equation modeling was used to explore the components influencing farmers' drought adaptation behaviors. Results and discussion According to the results, personal norms, attitudes, objective barriers, and subjective barriers had positive and significant effects on the farmers' intention to apply drought adaptation strategies. As well, the farmers' adaptation behaviors were influenced by their behavioral intentions, objective barriers, and subjective barriers. It can be concluded that changing the mechanism of farmers' behaviors toward drought adaptation is shaped by the processes included in the comprehensive action determination model in which norms, habits, situational influences, and intentional processes are involved.